Biomarkers in kidney disease - Edelstein, Charles L. (Charles Louis) (Academic Press/Elsevier, 2010)
A biomarker is a molecule that is measured as a marker of normal biological processes, disease processes or the response to a diagnostic or therapeutic intervention. Kidney diseases like acute kidney injury, chronic kidney disease, diabetic nephropathy, glomerular disease, renal cancer and preeclampsia still have a high morbidity. Measurement of biomarkers in the blood or urine that detect patients at risk of kidney diseases or that detect kidney diseases in the earliest stage may ultimately result in preventative or earlier or more effective treatments for kidney diseases. Biomarkers of Kidney Disease & nbsp;reviews the basic and clinical research on biomarkers of the common kidney diseases including acute kidney injury, chronic kidney disease, renal cancer, diabetic nephropathy, glomerular disease and preeclampsia. The characteristics of an ideal biomarker of kidney diseases and statistical analysis of biomarker studies is detailed. The latest techniques for biomarker detection like metabolomics and proteomics is covered in the book. This comprehensive book details the latest advances made in the field of biomarker research and development in kidney diseases. The book is an ideal companion for those interested in biomarker research and development, proteomics and metabolomics, kidney diseases, statistical analysis, transplantation and preeclampsia. * Presents a comprehensive, translational source for all aspects of renal biomarkers in one reference work * Experts in renal disease biomarkers (from all areas of academic and medical research) take readers from the bench research (cellular and molecular mechanism) to new therapeutic approaches.